Extended user experience model to support web accessibility and emotional qualities among visually impaired users - Jantan, Azrul Hazri; Yazid, Mariam Azwa; Mubin, Siti Azreena (Karadeniz Technical University, 2021)
To date, the advancement inmobile applications and Internet technologies have changed the way on howpeople interact with computer software/application.Information is much easier to accessed, processes can be performed faster, and interaction can be controlled fully by users.This paper will elaborateand discuss the information and interaction processes taken between users and computer software/applicationaccording to the existing user experience model.The main objective is to present an extension ofuser experience model that to support the interaction between users and applicationsamong the disabilities (visually impaired). It will include better technology understanding on both conceptual and interaction properties of the whole application domain and their associations between web accessibility, user experience, and technology acceptance. The proposed model will be focusing on two parts; user experience components, and consequences (outcome). It will be used in further empirical study on modeling the relationships between the application users, user experience, and technology acceptance. We envisage effective and comprehensive design model that could be integrated and provide positive progress from the existing literature findings.